External beam radiation after stent implantation increases neointimal hyperplasia by augmenting smooth muscle cell proliferation and extracellular matrix accumulation - Hehrlein, Christoph; Kaiser, Simone; Riessen, Reimer; Metz, Jürgen; Fritz, Peter; Kübler, Wolfgang (Journal of the American College of Cardiology, 2000)
OBJECTIVES: We sought to examine the effects of high volume external beam radiation (EBR) after stent implantation on neointimal hyperplasia, smooth muscle cell (SMC) proliferation, presence of inflammatory cells and expression of extracellular matrix (ECM). BACKGROUND: Endovascular irradiation has been shown to reduce restenosis rates after angioplasty in preliminary trials, but conflicting results have been reported for the effects of external beam irradiation. METHODS: Forty-three Palmaz-Schatz stents were implanted into iliac arteries of New Zealand White rabbits. The arteries were externally irradiated after stent implantation with a single dose of 8 Gy (at day 3) or 16 Gy in two fractions (8 Gy at days 3 and 4) by means of a linear accelerator. In the control rabbits, no radiation was applied after stent implantation. Smooth muscle cells, macrophages and ECM were studied by immunohistochemistry at one and 12 weeks after stent implantation. Collagen type I and biglycan messenger ribonucleic acid (mRNA) levels were assessed by Northern blot analysis at one week. Neointimal cell densities and arterial lumen stenosis were measured by histomorphometry at 12 weeks. RESULTS: At 1 week, SMC proliferation at the site of stent implantation was increased after EBR with 8 and 16 Gy (26 ± 5%, 32 ± 3% vs. 17 ± 8%; p < 0.01, 16 Gy vs. control). External beam radiation with 8 and 16 Gy augmented SMC proliferation proximal and distal to the angioplasty site (11 ± 3%, 14 ± 3 vs. 6 ± 1%; p < 0.01, 16 Gy vs. control). Collagen type I and biglycan mRNA levels were elevated in stented arteries after EBR with 16 Gy. At 12 weeks, a marked decrease in neointimal cell density (248 ± 97 vs. 498 ± 117 SMCs/0.1 mm2neointima; p < 0.005 vs. control) was noted after EBR with 16 Gy. Irradiation with 8 and 16 Gy increased arterial lumen stenosis compared with nonirradiated control rabbits (45 ± 7%, 55 ± 9% vs. 33 ± 7%; p < 0.05, 8 Gy and p < 0.001, 16 Gy vs. control). CONCLUSIONS: High volume external beam radiation at doses of 8 or 16 Gy causes restenosis by augmenting proliferative activity at and adjacent to the site of stent implantation, and by dose-dependent up-regulation of extracellular matrix expression. The study suggests that excessive matrix accumulation is an important determinant of failure of radiation therapy to prevent restenosis.